Estimated incidence of noma "A biologic indicator of poverty" in north central Nigeria: A retrospective cross-sectional study - Bello, Seidu Adebayo; Adeoye, John Ademola; Oketade, Ifeoluwa; Akadiri, Oladimeji (bioRxiv, 2019)
Background: Noma is a spreading and devouring disease which is believed to be native to Sub-Saharan Africa over the last decade due to poverty. Within this noma belt, most epidemiological reports regarding the disease have emanated from the north western region of Nigeria. However, our indigenous surgical mission encountered a substantial number of cases noteworthy of epidemiological representation in north central Nigeria. Methods: All facial cleft and noma cases encountered within the 8 year study period were included into this study. Estimated incidence of the noma in the zone was calculated using the existing statistical model of Fieger et al (2003), which takes into account the expected differences based on age and location of the two patient groups using the multinomial logistic regression analysis. Period prevalence of noma was also calculated by simple division considering the population at risk of the disease in the zone. Findings: A total of 770 subjects were included in this study (orofacial cleft 692, noma 78). The incidence estimate of noma in the north central zone was 3.2 per 1000 with a range of 2.6 to 3.7 per 1000. The period prevalence of noma was 1:125,000 children. The median age of noma patients was comparatively higher than the median age of facial cleft patients. The mean age of onset of noma was 5.9 + 8.08 years which was lower than the average age of individuals in the noma group (29.6 + 18.84 years). Conclusion: Although noma may be more prevalent in the north western region of Nigeria; substantial number of cases is still being encountered in the north central zone which calls for urgent attention of relevant health stakeholders regarding the management and rehabilitation of individuals affected.